INTENSITAS CAHAYA ALAMI PADA RUANG KELAS PERKULIAHAN: Studi Kasus: Ruang Perkuliahan Universitas Bosowa - Muh. Awaluddin Hamdy; Nurul Jamala; Ramli Rahim; Baharuddin Hamzah; Rosady Mulyadi; Asniawaty Kusno (ATRIUM: Jurnal Arsitektur, 2019)
Title: Natural Light Intensity Analysis in Classroom; Case Study: Classroom at Bosowa University Lighting is an important part of buildings in supporting the productivity of human labor. Insufficient lighting can interfere with human activities and could cause health problems, like eye disorders. Building design must consider the functions and needs so that residents can feel comfortable. Good lighting levels can be achieved by utilizing natural and artificial lighting. The purpose of this study was to analyze the level of illumination in a room that is directly related to the openings of the building envelope and to analyze the different levels of illumination in classrooms with different orientations. Quantitative research methods by distributing measurement data in the form of tables, diagrams and graphs. Data analysis was performed using statistics and data analysis techniques, the results of the measurement were statistically descriptive. This study analyzed the differences in the level of illumination in the northern orientation and southern orientation classrooms. Based on the results of the analysis it can be concluded that the orientation of the building affects the level of illumination in the room. During the day the level of illumination is higher in the direction of orientation north than the direction of orientation south, especially the measurement point in the area close to the openings of the building envelope, but in this study the direction of classroom orientation towards the south is higher the level of illumination compared to the north orientation classrooms. This is understood by the treatment of building glass sheaths in the north orientation direction in the form of the use of frosted glass wallpaper, so it can be concluded that changes to the building facade affect the level of room illumination. The results of this study are expected to be a reference in building facade concepts and designing energy-efficient buildings.